Spatiotemporal variability of satellite-derived abundance of Karenia spp. during 2021 in shelf waters along the Pacific coast of Hokkaido, Japan - Kuroda, Hiroshi; Takagi, Satomi; Azumaya, Tomonori; Hasegawa, Natsuki (Frontiers in Marine Science, 2024)
Unprecedented catastrophic damage to coastal fisheries attributable to harmful Karenia outbreaks were reported in Pacific coastal shelf waters off the southern coast of Hokkaido from late summer to autumn in 2021. To understand the spatiotemporal variability of the Karenia blooms, we analyzed Sentinel 3-derived abundances of Karenia spp. together with marine environmental variables. Karenia spp. were very widely distributed over a maximum of more than 400 km along the shelf from the easternmost Pacific coast of Hokkaido to Cape Erimo, where there was a nearly stable water-mass front, to the west, where pure subtropical water inhibited the westward expansion of Karenia spp. blooms. The duration of the appearance of Karenia spp. at a fixed point was very long—about 45 days—in the middle part of the shelf. East of the Tokachi River, the time-averaged abundances of Karenia spp. were robustly correlated with the time-averaged alongshore velocity and stability of the Coastal Oyashio, a coastal boundary current; more intense and stable alongshore currents were associated with less developed Karenia spp. blooms. Time-averaged abundances of Karenia spp. were the highest in the middle part of the shelf, west of the Tokachi River, where low-salinity water from the river suppressed the development of the surface winter mixed layer and might have fostered favorable growth conditions and supplied nutrients of land origin. During the period of Karenia spp. blooms, abundances changed rapidly on a small scale (typically, ≤2 days and ≤50 km) in association with physical-biochemical coupled submesoscale variations. Subsampling of these variations of Karenia spp. abundances at 1-day intervals showed that the maxima and center of gravity of Karenia spp. abundances moved slowly westward along the coast at a typical velocity of 4 cm s−1. This velocity was one-third that of the time-averaged alongshore velocity of the Coastal Oyashio. Particle-tracking experiments implied that horizontal advection by the Coastal Oyashio, which supplied Karenia spp. eliminated from the upstream shelf to the downstream shelf, contributed to the long duration of Karenia spp. blooms on the middle part of the shelf.